2014
DOI: 10.1136/neurintsurg-2014-011475
|View full text |Cite
|
Sign up to set email alerts
|

Technology developments in endovascular treatment of intracranial aneurysms

Abstract: Advances in the management and endovascular treatment of intracranial aneurysms are progressing at a tremendous rate. Developments in novel imaging technology may improve diagnosis, risk stratification, treatment planning, intraprocedural assessment, and follow-up evaluation. Evolution of devices, including microwires, microcatheters, balloons, stents, and novel scaffolding devices, has greatly expanded the potential to treat difficult aneurysms. Although developments in technology have greatly improved the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Moreover, the stent can provide the bridge by which vascular endothelial cells can cover the BBA neck 47. In most cases, stent-assisted coil therapy is feasible; for example, in 2008, Korja et al reported on patient with a BBA of the supraclinoid ICA who underwent stent-assisted coil embolization in the acute stage of SAH and the long-term follow-up outcome was good; therefore, stent-assisted coil embolization of ruptured BBAs in the acute stage appears to be a technically feasible treatment option 48.…”
Section: Endovascular Treatment To Repair the Supraclinoid Icamentioning
confidence: 99%
“…Moreover, the stent can provide the bridge by which vascular endothelial cells can cover the BBA neck 47. In most cases, stent-assisted coil therapy is feasible; for example, in 2008, Korja et al reported on patient with a BBA of the supraclinoid ICA who underwent stent-assisted coil embolization in the acute stage of SAH and the long-term follow-up outcome was good; therefore, stent-assisted coil embolization of ruptured BBAs in the acute stage appears to be a technically feasible treatment option 48.…”
Section: Endovascular Treatment To Repair the Supraclinoid Icamentioning
confidence: 99%
“…Due to the absence of a major dural venous sinus in the ACF, DAVF located in this region uniformly drain directly into cortical veins and frequently cause venous ectasia [4]. Since ACF DAVF are supplied by ethmoidal branches of the ophthalmic artery, neurointerventionalists have traditionally been reluctant to embolize these lesions, although recent technological advances have made safe endovascular treatment feasible [5][6][7]. Nevertheless, surgical ligation remains the preferred treatment for ACF DAVF [8].…”
Section: Introductionmentioning
confidence: 98%
“…Side-branch occlusion seems to occur more commonly in the posterior circulation than the anterior circulation [55][56][57]. De Vries et al [42] reported absence of anterograde flow on 6-month follow-up after Surpass implantation in 2 out of 15 cases of covered ophthalmic arteries (15%) and 4 out of 15 cases of covered posterior communicating arteries (31%), fortunately without neurological symptoms.…”
Section: Thromboembolic and Ischemic Complicationsmentioning
confidence: 99%
“…Delayed Hemorrhage Delayed complications, usually beyond 48 h after procedure such as intraparenchymal hemorrhage and SAH are critical, and develop in 3 and 4% of cases, respectively [57,113]. Most alarming is distal intraparenchymal hemorrhages that have been reported weeks to months after flow diversion.…”
Section: Delayed Complicationsmentioning
confidence: 99%